siRNA as a Potential Therapy for COVID-19 - Aljaberi, Ahmad; Migdadi, Eman M.; Khadra, Khalid M. Abu; Samak, Mahmoud A.; Basheti, Iman A.; Al-Zoubi, Nizar (Current Drug Delivery, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) is a highly contagious virus causing COVID-19 disease that severely impacted the world health, education, and economy systems in 2020. The numbers of infection cases and reported deaths are still increasing with no specific treatment identified yet to halt this pandemic. Currently, several proposed treatments are under preclinical and clinical investigations now, alongside the race to vaccinate as many individuals as possible. The genome of SARS-CoV2 shares a similar gene organization as other viruses in the Coronaviridae family. It is a positive-sense, single-stranded RNA. This feature suggests that RNA interference (RNAi) is an attractive prophylactic and therapeutic option for the control of this pandemic and other possible future pandemics of the corona viruses. RNAi utilizes the use of siRNA molecules, which are 21-29 nt duplexes RNA molecules that intervene with targeted gene expression in the cytoplasm by a specific mechanism of complementary destruction of mRNA. Previous experience with SARS-CoV and the Middle East respiratory syndrome (MERS) showed that siRNA molecules were effective against these viruses in vitro and in vivo. Moreover, there have been extensive advances in siRNA technology in the past decade from chemistry and target selection considerations; which concluded with the successful approval of two commercial products based on siRNA technology. In addition, the current knowledge of the genome structure and functionality of the corona viruses enables the recognition of conserved sequences to optimize siRNA targeting and avoid viral escape through mutations, either for the current SARS-CoV2 as well as future corona viruses.
Keywords: Corona viruses